The effect of batched patient–physician assignment on patient length of stay in the emergency department - Bryan Imhoff; Kenneth D. Marshall; Joshua W. Joseph; Nima Sarani; Julie Kelman; Niaman Nazir (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Queuing theory suggests that signing up for multiple patients at once (batching) can negatively affect patients’ length of stay (LOS). At academic centers, resident assignment adds a second layer to this effect. In this study, we measured the rate of batched patient assignment by resident physicians, examined the effect on patient in‐room LOS, and surveyed residents on underlying drivers and perceptions of batching. Methods This was a retrospective study of discharged patients from August 1, 2020 to October 27, 2020, supplemented with survey data conducted at a large, urban, academic hospital with an emergency medicine training program in which residents self‐assign to patients. Time stamps were extracted from the electronic health record and a definition of batching was set based on findings of a published time and motion study. Results A total of 3794 patients were seen by 28 residents and ultimately discharged during the study period. Overall, residents batched 23.7% of patients, with a greater rate of batching associated with increasing resident seniority and during the first hour of resident shifts. In‐room LOS for batched assignment patients was 15.9 minutes longer than single assignment patients (P value < 0.01). Residents’ predictions of their rates of batching closely approximated actual rates; however, they underestimated the effect of batching on LOS. Conclusions Emergency residents often batch patients during signup with negative consequences to LOS. Moreover, residents significantly underestimate this negative effect.